Media Presentasi Dalam Bentuk Motion Graphic (Studi Kasus: Proses Produksi Detak Kepri Malam Batam Tv) - Evaliata Br Sembiring (Politeknik Negeri Batam, 2022)
Apprentices at Batam TV are required to understand the production process at Batam TV, such as the production process for the Detak Kepri Malam, and other programs. The presentation of the material is delivered through presentations using the PowerPoint application and presented by the presenter. The level of visits is very high, taking up Batam TV's time for presentations. The solution offered is the presentation of material in the form of motion graphics. The research method uses RnD, namely making presentation material products in the form of motion graphics using the Villamil-Molina method, then analyzing the application of motion graphic aspects and presentation material aspects using Quasi Experiment Nonequivalent Control Group Design through a Paired sample T-test. The results showed that the media presentation to explain the production process of Detak Kepri Malam in video form was considered effective. The video lasts 2 minutes 30 seconds and is in Mp4 format and is displayed using a prompter in the Batam TV broadcast studio so it doesn't depend on the presenter of the material, and is easy to access via the Batam TV YouTube channel.